2021
DOI: 10.3389/fcell.2021.715200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in the Maintenance of Stemness in Adult Stem Cells: A Disease-Relevant Mechanism of Action

Abstract: Autophagy is an intracellular scavenging mechanism induced to eliminate damaged, denatured, or senescent macromolecular substances and organelles in the body. The regulation of autophagy plays essential roles in the processes of cellular homeostasis and senescence. Dysregulated autophagy is a common feature of several human diseases, including cancers and neurodegenerative disorders. The initiation and development of these disorders have been shown to be associated with the maintenance of disease-specific stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…Apparently, in contradiction with the SA-β-gal activity, our findings agree with reduced autophagy in senescent cells which is considered one of the hallmarks of senescence and aging [ 42 , 43 , 44 ]. Furthermore, a key role of autophagy in survival has been demonstrated, stem cell maintenance and tissue homeostasis, which sustains the stemness in stem cells and delays stem cell senescence [ 41 , 45 ]. These data could explain the high level of lysosomes in healthy sf-MSCs, which could be involved in autophagy as a fundamental mechanism to keep their self-renewal ability.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, in contradiction with the SA-β-gal activity, our findings agree with reduced autophagy in senescent cells which is considered one of the hallmarks of senescence and aging [ 42 , 43 , 44 ]. Furthermore, a key role of autophagy in survival has been demonstrated, stem cell maintenance and tissue homeostasis, which sustains the stemness in stem cells and delays stem cell senescence [ 41 , 45 ]. These data could explain the high level of lysosomes in healthy sf-MSCs, which could be involved in autophagy as a fundamental mechanism to keep their self-renewal ability.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported the impact of autophagy on regulating Notch1 signaling. Autophagy mediates Notch1 receptor degradation by being captured by pre-autophagosome vesicles (Casares-Crespo et al 2018 ; Chen et al 2021 ). In turn, activation of Notch1 signaling exacerbates I/R-induced inflammatory injury by means of an upregulated NLRP3 inflammasome (Jin et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kupffer cells, resident macrophages invading the Disse space, are the largest population of hepatic immune cells ( 28 ). There are two Kupffer subpopulations: the M1 CD68+ subset with phagocytic capacity and producing nitric oxide (NO) and ROS and the M2 CD11b+ subgroup that produces cytokines, like IL-10 and IL-12.…”
Section: Immune Cells and Liver Immunologymentioning
confidence: 99%
“…Overall, a reduction of autophagy may act as a tumor-promoting factor by reducing hepatocyte quality and increasing genomic damage, whereas its upregulation may favor the elimination of products originating from metabolic stress and cytotoxic chemotherapy. Furthermore, since autophagy is able to eliminate the mutant p53 tumor suppressor, one of the most frequent mutated protein involved in the proliferation and survival of liver stem cells, a reduction in autophagy favors the maintenance of hepatic stem cells, which play a key role in supporting cancer cells and in promoting tumor recurrence and resistance to therapy ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%